Breast pericytes: a newly identified driver of tumor cell proliferation - Del Toro, Katelyn; Licon-Munoz, Yamhilette; Crabtree, William; Oper, Tristan; Robbins, Christine; Hines, William C. (Frontiers in Oncology, 2024)
IntroductionEffective treatment of breast cancer remains a formidable challenge, partly due to our limited understanding of the complex microenvironmental factors that contribute to disease pathology. Among these factors are tissue-resident perivascular cells, which play crucial roles in shaping vascular basement membranes, maintaining vessel integrity, and communicating with adjacent endothelial cells. Despite their essential functions, perivascular cells have been relatively overlooked. Identifying them by immunostaining has been challenging due to their low abundance, inherent heterogeneity, and shared marker expression with other cell types. These challenges have hindered efforts to purify pericytes and generate primary cell models for studying their biology.MethodsUsing a recently developed FACS method, we successfully identified and purified each cell type from breast tissues, allowing us to deep-sequence their transcriptomes and generate primary cell models of each cell type—including pericytes. Here, we used these data to analyze cell-type-specific gene expression in tumors, which revealed a strong association between pericyte-specific genes and breast cancer patient mortality. To explore this association, we defined the heterogeneity of breast pericytes using single-cell RNA sequencing and identified a broad marker for visualizing perivascular cells in breast tumors.ResultsRemarkably, we discovered perivascular cells dissociated from vessels and emerged as a dominant mesenchymal cell type in a subset of breast tumors that contrasted with their normal perivascular location. Moreover, when we purified pericytes from the breast and cultured them alongside breast tumor cells, we discovered that they induced rapid tumor cell growth significantly greater than isogenic fibroblast controls.DiscussionThese findings identify perivascular cells as a key microenvironmental factor in breast cancer, highlighting the critical need for further research to explore their biology and identify specific stimulatory mechanisms that could be targeted therapeutically.